FROM EUCLID TO THE AGE OF THE IMAGE - Kourniatis, Nikolaos (Design/Arts/Culture, 2020)
This paper attempts to give an interpretation of the importance of the role of geometry and in particular the courses of perspective in the formation of the perception of space, in the architectural education. A role that seems to focus both on understanding methods of handling space and its objects, as well as on redefining the real-imaginary relationship; physical – virtual, collective - subjective. This inquiry begins with the axioms of Euclid’s Optics, from the period of Girard Desargues to the modern era, placing three different phases in the evolution of the formation of the perception of space, through the sense of vision. In the last part of the work, an application of perspective image remodeling is presented, through mirrors that are placed in an existing space. (fig.1) Geometry plays a dual role in the educational process of architects. On the one hand it aims to interpret the association between the different elements of space by frequently questioning established stimulus-response relations. The pattern of geometric thinking starts with observation and through analysis and questioning - which is a stage defined by its intense illusory nature; it ends up formulating rules and eventually leads to new interpretations of disciplines and relationships that are already known.